Swapping the Gene-Specific and Regional Silencing Specificities of the Hst1 and Sir2 Histone Deacetylases - Mead, Janet (American Society for Microbiology, 2007)
Sir2 and Hst1 are NAD(+)-dependent histone deacetylases of budding yeast that are related by strong sequence similarity. Nevertheless, the two proteins promote two mechanistically distinct forms of gene repression. Hst1 interacts with Rfm1 and Sum1 to repress the transcription of specific middle-sporulation genes. Sir2 interacts with Sir3 and Sir4 to silence genes contained within the silent-mating-type loci and telomere chromosomal regions. To identify the determinants of gene-specific versus regional repression, we created a series of Hst1::Sir2 hybrids. Our analysis yielded two dual-specificity chimeras that were able to perform both regional and gene-specific repression. Regional silencing by the chimeras required Sir3 and Sir4, whereas gene-specific repression required Rfm1 and Sum1. Our findings demonstrate that the nonconserved N-terminal region and two amino acids within the enzymatic core domain account for cofactor specificity and proper targeting of these proteins. These results suggest that the differences in the silencing and repression functions of Sir2 and Hst1 may not be due to differences in enzymatic activities of the proteins but rather may be the result of distinct cofactor specificities.